PENYUSUNAN STANDARD OPERATIONAL PROCEDURE PRODUKSI PADA BISNIS BAKSO PEPO - William Wijaya (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
This research contains the preparation of Standard Operating Procedure (SOP) in the production of Bakso Pepo. This research begins by complaints from Bakso Pepo’s customers that are mostly derived from the production. This research aimed to develop a SOP right to apply to the business of Bakso Pepo. Sampling was done to pre-survey respondents who have purchased Bakso Pepo’s product at least three times. Methods of data collection using qualitative methods of using a semi-structured interview, observation and documentation of data research firm. Number of speakers who made respondents to the needs of research data consists of 4 people consisting of 2 similar companies, and two SOP production experts. Checking the validity and reliability of data using the validity of the data that is triangulation of sources and techniques, namely by comparing data available from various sources. Data analysis was performed using the method of data analysis according to Miles and Huberman of reduction, data presentation, and conclusion. This research study presents a profile of the company, the drafting of the initial SOP, SOP production flowchart manufacture, and testing SOP production. Results from this research are making the Standard Operational Procedure (SOP) in the production of Bakso Pepo.